2019
DOI: 10.1029/2019gl084657
|View full text |Cite
|
Sign up to set email alerts
|

Iron Supply Pathways Between the Surface and Subsurface Waters of the Southern Ocean: From Winter Entrainment to Summer Storms

Abstract: Dissolved iron (DFe) plays an immeasurable role in shaping the biogeochemical processes of the open-ocean Southern Ocean. However, due to observational constraints iron supply pathways remain poorly understood. Using an idealized eddy-resolving physical-biogeochemical model representing a turbulent sector of the Southern Ocean with seasonal buoyancy forcing and zonal winds overlaid by storms, we quantify the importance of a range of subsurface and surface iron supply mechanisms. The main physical supply pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 55 publications
1
31
0
Order By: Relevance
“…3, 4). A study using a similar zonally re-entrant channel model, also found an increase in wintertime (August-October) vertical eddy iron transport, and consequently elevated primary production during September-October (29). Their spatial resolution of 1/24 , however, is similar to our 5 km run and the relative contribution of eddy transport in their study is likely underestimated (Fig.…”
Section: Implications For Iron Budgets and Biogeochemical Modellingsupporting
confidence: 67%
See 1 more Smart Citation
“…3, 4). A study using a similar zonally re-entrant channel model, also found an increase in wintertime (August-October) vertical eddy iron transport, and consequently elevated primary production during September-October (29). Their spatial resolution of 1/24 , however, is similar to our 5 km run and the relative contribution of eddy transport in their study is likely underestimated (Fig.…”
Section: Implications For Iron Budgets and Biogeochemical Modellingsupporting
confidence: 67%
“…Deep iron concentrations of roughly 0.4 µmol Fe m 3 at 1000 m coincide with the observational mean in the ACC, while near-surface concentrations (0.05 µmol Fe m 3 ) are lower than the observational range. This discrepancy is likely due to the lack of aeolian, glacial and bathymetric sources (28), uncertainty in the ecosystem model parameters (11), and potentially due to the lack of storms which have been argued to enhance diffusive entrainment of iron from the interior (29). As a result, iron is the limiting nutrient year round in our simulations, while in the real ACC, silicate limitation is also expected to control diatom growth and transition in phytoplankton community composition (8; 9).…”
Section: Submesoscale Permitting Simulation Of the Open Southern Oceamentioning
confidence: 99%
“…3 and 4). A study using a similar zonally re-entrant channel model, also found an increase in wintertime (August-October) vertical eddy iron transport, and consequently elevated primary production during September-October 28 . Their spatial resolution of 1/24 ∘ , however, is similar to our 5 km run and the relative contribution of eddy transport in their study is likely underestimated (Fig.…”
Section: Discussionmentioning
confidence: 80%
“…Deep iron concentrations of roughly 0.4 μmol Fe m −3 at 1000 m coincide with the observational mean in the ACC, while near-surface concentrations (0.05 μmol Fe m −3 ) are lower than the observational range. This discrepancy is likely due to the lack of aeolian, glacial, and bathymetric sources 27 , uncertainty in the ecosystem model parameters 10 , and potentially due to the lack of storms which have been argued to enhance diffusive entrainment of iron from the interior 28 . As a result, iron is the limiting nutrient year round in our simulations, while in the real ACC, silicate limitation is also expected to control diatom growth and transition in phytoplankton community composition 7,8 .…”
Section: Submesoscale Permitting Simulation Of the Open Southernmentioning
confidence: 99%
“…They proposed that the observed MLD variability was responsible for regulating light and iron supply to surface waters at appropriate time scales for phytoplankton growth, thereby sustaining the SAZ phytoplankton bloom into late summer. Since then, there have been a number of additional studies which suggest that in addition to deep winter entrainment and recycling (Tagliabue et al, 2014), intermittent storm-driven mixing may play an important role in extending the duration of summertime production in the SAZ and other regions through intraseasonal entrainment of iron from a subsurface reservoir beneath the productive layer (Smith et al, 2011;Carranza and Gille, 2015;Thomalla et al, 2015;Nicholson et al, 2016Nicholson et al, , 2019Mtshali et al, 2019). As an example, Mtshali et al (2019) examined the seasonal evolution of dissolved iron profiles at a single station in the SAZ to explore different mechanisms driving iron availability (convective mixing, biological consumption, scavenging, recycling, and entrainment).…”
Section: Npq Max (Figuresmentioning
confidence: 99%